Pattern and trend of bacterial resistance in neonatal sepsis in infants admitted to the neonatal intensive care unit, from 2016 to 2021 - Amir Naddaf; Mohammad Ansari Nasab; Mamak Shariat; Parvaneh Sadeghi-Moghaddam; Samaneh Salarvand; Zahra Omidi; Neda Sadat Kosari; Leyla Sahebi (Iranian Journal of Microbiology)
Background and Objectives: Neonatal septicemia is a significant cause of morbidity and mortality in neonatal intensive care units (NICUs). Understanding the patterns of antibiotic resistance and pathogen prevalence is crucial for effective treatment. Materials and Methods: This cross-sectional study was conducted from 2016 to 2022 in the NICU of Vali-Asr Hospital in Tehran. All neonates diagnosed with septicemia were included. Data were collected using the hospital's registry system. Results: A total of 477 infants were hospitalized with sepsis, with 71.7% classified as early-onset sepsis (EOS) and 28.3% as late-onset sepsis (LOS). The most common pathogens were coagulase-negative Staphylococcus (22.1%), Klebsiella pneumoniae (14.9%), and Staphylococcus epidermidis (14.3%). The highest antibiotic resistance was observed for erythromycin (89.8%), clindamycin (80.6%), gentamicin (66.1%), and ciprofloxacin (63.5%), while vancomycin showed the lowest resistance (11.2%). Significant associations were found between antibiotic resistance with low birth weight and chest tube intervention. Trends in antibiotic resistance varied over the study period, with a notable decrease in resistance in 2021. Conclusion: The study highlights the high prevalence of antibiotic resistance in neonatal sepsis, emphasizing the need for continuous monitoring and tailored antibiotic stewardship programs. The findings underscore the importance of individualized treatment approaches to improve outcomes for neonates with sepsis.